Responsive Interaction in Dynamic Envelopes with Mesh Tessellation - Datta, Sambit; Andrei, S.; Chang, T. (2016)
The paper will report on an ongoing experimental research collaboration to develop a conceptual architectural envelope that responds to feedback from external stimuli. The paper builds on our research on the construction of interactive envelope components based on the manipulation of mesh tessellations and the development of responsive interaction with architectural elements. In the context of our research, chameleon ceiling looks at ways to integrate various systems (geometric, structural and electronic-responsive) and their effects on modular, component-driven systems construction through computation and digital fabrication.